2009
DOI: 10.1038/hdy.2009.135
|View full text |Cite
|
Sign up to set email alerts
|

The consequences of winter flock demography for genetic structure and inbreeding risk in vinous-throated parrotbills, Paradoxornis webbianus

Abstract: The adaptive significance of flocking behaviour has been intensively studied, especially among birds, but the demography and genetic structure of winter flocks is poorly understood, despite their importance for many biological processes. For three successive winters, we studied the demography and genetic structure of winter flocks in a small passerine, the vinous-throated parrotbill Paradoxornis webbianus. Our objectives were to determine the match between observed demography and the genetic structure of winte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 72 publications
0
24
0
Order By: Relevance
“…This was found in wild populations of great tits (Parus major) separated by distances of o3 km (Garant et al, 2005;Shapiro et al, 2006;Björklund et al, 2010), and also in song sparrows (Melospiza melodia) with five subspecies coexisting in a restricted area made of various microhabitats (Chan and Arcese, 2003). However, the latter results were not associated with significant neutral genetic differentiation, which suggests that genetic drift was not strong enough to generate neutral genetic differentiation (but also refer to the studies by Senar et al (2006), Lee et al (2010) and Rutz et al (2012)). There is no evidence from previous studies that populations belonging to one particular colour form of the Réunion grey white-eye and being as geographically close as those used in this study show any sign of niche differentiation (Gill, 1971(Gill, , 1973, suggesting that this explanation is unlikely.…”
Section: Genetic Differentiation With No Geographic and Ecological Trmentioning
confidence: 79%
“…This was found in wild populations of great tits (Parus major) separated by distances of o3 km (Garant et al, 2005;Shapiro et al, 2006;Björklund et al, 2010), and also in song sparrows (Melospiza melodia) with five subspecies coexisting in a restricted area made of various microhabitats (Chan and Arcese, 2003). However, the latter results were not associated with significant neutral genetic differentiation, which suggests that genetic drift was not strong enough to generate neutral genetic differentiation (but also refer to the studies by Senar et al (2006), Lee et al (2010) and Rutz et al (2012)). There is no evidence from previous studies that populations belonging to one particular colour form of the Réunion grey white-eye and being as geographically close as those used in this study show any sign of niche differentiation (Gill, 1971(Gill, , 1973, suggesting that this explanation is unlikely.…”
Section: Genetic Differentiation With No Geographic and Ecological Trmentioning
confidence: 79%
“…Although we could not discern flock membership of the individuals used in this study, within‐flock genetic structures in P. webbianus were found to be seasonally unstable and were not strong enough to create inbreeding (Lee et al . , ). In addition, home ranges of neighbouring P. webbianus flocks could overlap extensively with membership changes under some circumstances (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…However, I found patchy distribution of EPP among females, and in three nests with multiple EPY there was only one extra-pair male per brood. Interestingly, Lee et al (2010) reported that winter flocks of vinous-throated parrotbills where pairing occurs are genetically structured. Even males and females within the same flocks showed a higher degree of genetic relatedness than those between flocks.…”
Section: Discussionmentioning
confidence: 99%
“…In order to identify juvenile recruitment, I also caught birds at the surrounding area in the second and third wintering seasons (16 flocks with 30-160 individuals, capture rate: [60% in most flocks; see Lee et al 2010 for the map of flock locations). Almost all birds caught in winter were ringed with metal rings and given unique combinations of color rings.…”
Section: Methodsmentioning
confidence: 99%